Navigating Career Choices: Motivating And Demotivating Factors Among Students In University Of Peshawar - Muhammad Osama , Muhammad Bilal , Waqas Ahmad , Yasir Zaman , Roohullah Khan , Abdu Rahman , Ajmal Hussain , Usman Ali Khan (Migration Letters, 2024)
Career selection is a critical decision impacting individuals’ future trajectories, income, social status, and emotional well-being. This study investigates the motivating and demotivating factors influencing career choices among intermediate students in Peshawar, Pakistan. Conducted at the University of Peshawar, the research employs a cross-sectional descriptive design with a sample of 300 students. Findings reveal that "Personal Interest" is the primary motivating factor for both male (62.42%) and female (66.92%) students, while "Fear of Uncertainty" is the dominant demotivating factor for both genders, affecting 29.47% of males and 38.58% of females. These results indicate th[1]at students are driven by their passions but hindered by uncertainties regarding future outcomes. The study highlights the necessity for educators and career counselors to focus on students’ interests and provide robust guidance to alleviate uncertainties. This approach can help students make informed career choices, enhancing their motivation and dedication. The research contributes to existing literature on career development, emphasizing the importance of personal interest and addressing fears in career decision-making. Future research should consider diverse student populations and explore additional factors influencing career choices to develop comprehensive career guidance programs.